Combination Epigenetic Therapy in Advanced Breast Cancer with 5-Azacitidine and Entinostat: a Phase II National Cancer Institute/Stand Up to Cancer Study - Connolly, Roisin M (Clin Cancer Res, 2016)
PURPOSE: In breast cancer models, combination epigenetic therapy with a DNA methyltransferase inhibitor and a histone deacetylase inhibitor led to re-expression of genes encoding important therapeutic targets including the estrogen receptor (ER). We conducted a multicenter phase II study of 5-azacitidine (AZA) and entinostat in women with advanced hormone-resistant or triple-negative breast cancer (TNBC). PATIENTS AND METHODS: Patients received AZA 40 mg/m(2) (days 1–5, 8–10) and entinostat 7 mg (days 3,10) of 28 day cycle. Continuation of epigenetic therapy was offered with addition of endocrine therapy at time of progression (optional continuation, OC phase). Primary endpoint was objective response rate (ORR) in each cohort. We hypothesized that ORR would be ≥20% against null of 5% using Simon two-stage design. At least 1 response was required in 1(st) of 13 patients per cohort to continue accrual to 27 per cohort. Type I error 4%, power 90%. RESULTS: There was one partial response among 27 women with hormone-resistant disease (ORR=4%, 95% CI=0–19%), and none in 13 women with TNBC. One additional partial response was observed in the OC phase in the hormone-resistant cohort (n=12). Mandatory tumor samples were obtained pre- and post-treatment (58% paired) with either up- or down-regulation of ER observed in approximately 50% of post-treatment biopsies in the hormone-resistant, but not TNBC cohort. CONCLUSION: Combination epigenetic therapy was well tolerated but our primary endpoint was not met. OC phase results suggest that some women benefit from epigenetic therapy and/or reintroduction of endocrine therapy beyond progression but further study is needed.